Spatial, monthly, and interannual distribution patterns of the non-indigenous Peach Blossom Jellyfish Craspedacusta sowerbii in British Columbian freshwater systems - Lüskow, Florian; Pakhomov, Evgeny A (PANGAEA, 2024)
A globally distributed aquatic non-indigenous species is the hydrozoan Craspedacusta sowerbii. The species' northern distribution boundary in North America is situated in British Columbia (BC), Canada. It is thus of paramount interest to understand its spatiotemporal ecology in the invaded warming habitat, which would allow knowledge transfer to other regions. Currently, C. sowerbii has been reported in BC since August 1990 in 34 freshwater systems (3 on the Lower Mainland, 11 on the Sunshine Coast, 17 on Vancouver Island, and 3 at other locations). These freshwater systems (lakes, ponds, and quarries) are generally shallow (< 10 m), most often of a natural origin, and have a small surface area (< 0.1 km²). A nearly exponential trend of medusa observations from 1990 till the end of the 2020s is noticeable. The first seasonal records are in July and the latest in October, while sighting peaks are reported in August and September.
Keywords: Cnidaria; Freshwater jellyfish; Hydrozoa; invasive species; Monitoring